Theory of high temperature superconductivity: A conventional approach - Mishonov, Todor M.; Penev, Evgeni S. (London: World Scientific, 2011)
Drawing from the broad spectrum of phenomena, described in more than 100,000 articles on high-Tc superconductivity, in this book, the authors analyze those basic properties for which understanding can be achieved within the framework of traditional methods of theoretical physics.This is the case of the overdoped cuprates for which the (3z(BBardeen program(3y (Bhas been realized: We know their electronic spectrum, we can calculate their basic thermodynamic and electrodynamic properties, and predict new phenomena. The book gives a pedagogical derivation of formulas describing the electron band structure, penetration depth, specific heat, fluctuation conductivity, etc. Prediction of plasmons and their application for a new type of THz generators is considered as well.The book advocates that the strongest exchange interaction in condensed matter physics $1 (Bthe intraatomic s-d exchange $1 (Bis the long sought pairing mechanism in overdoped cuprate superconductors.s
Include bibliographical references 225-255p.; Index 257-259p.
Keywords: Kinetic cooper pairs; Magnetic fields; Superconductivity; Thermodynamics; Physics